Parent-child relationship and child anger proneness in infancy and attachment security at toddler age: a short-term longitudinal study of mother- and father-child dyads. Issue 4 (4th July 2022) - Bendel-Stenzel, Lilly C.; An, Danming; Kochanska, Grazyna
ABSTRACT: Early parent-child relationship and child negative emotionality have both been studied as contributors to attachment security, but few studies have examined whether negative emotionality can moderate effects of parent-child relationship on security and whether the process is comparable across mother- and father-child dyads and different security measures. In 102 community families, we observed parent-child shared positive affect and infants' anger proneness at 7 months, and attachment security at 15 months, using observer-rated Attachment Q-Set (AQS) and a continuous measure derived from Strange Situation Paradigm (SSP). For mother-child dyads, high shared positive affect and low anger proneness were associated with AQS security. Those effects were qualified by their interaction: Variations in shared positive affect were associated with security only for relatively more anger-prone children. That effect reflected the diathesis-stress model. For father-child dyads, shared positive affect was associated with security. There were no effects for SSP security with either parent.